Dexamethasone as an Adjuvant to Lidocaine 2% and Levobupivacaine 0,5% in Transversus Abdominis Plane (TAP) Block after Appendectomy Surgery: A Case Report - Pradnya Niti, Ida Ayu Apsari; Albertus Medianto; Agus Suardhesana (HM Publisher, 2024)
Introduction: Post-appendectomy pain can hinder patient recovery and increase opioid consumption. TAP (transversus abdominis plane) block is an effective regional anesthetic technique for controlling pain after abdominal surgery. Dexamethasone, as an anti-inflammatory, can be added as an adjuvant to enhance the analgesic effect. Case presentation: This study describes the effectiveness of TAP block with adjuvant dexamethasone in patient A, a 17-year-old woman who underwent appendectomy. The patient received a TAP block with lidocaine 20 ml, levobupivacaine 10 ml, and dexamethasone 10 mg. Patient pain was measured using the numeric rating scale (NRS) at 1, 2, 6, 12, and 24 hours after surgery. Patients experienced low NRS values, even 0 at 1, 2, 6, 12, and 24 hours after surgery. Adjuvant dexamethasone to TAP block likely increases the analgesic effect and reduces opioid requirements. Conclusion: TAP block with adjuvant dexamethasone is an effective regional anesthesia technique for controlling post-appendectomy pain, increasing patient comfort, and speeding recovery.